Identification and Characterization of a Golgi-Localized UDP-Xylose Transporter Family from Arabidopsis. Issue 4 (24th March 2015) - Ebert, Berit; Rautengarten, Carsten; Guo, Xiaoyuan; Xiong, Guangyan; Stonebloom, Solomon; Smith-Moritz, Andreia M.; Herter, Thomas; Chan, Leanne Jade G.; Adams, Paul D.; Petzold, Christopher J.; Pauly, Markus; Willats, William G.T.; et al.
Abstract : Three nucleotide sugar transporters were shown to transport UDP-Xyl in vitro, demonstrating the existence of plant nucleotide sugar transporters with specificity for UDP-Xyl. UXT1 provides UDP-Xyl for cell wall biosynthesis. Abstract: Most glycosylation reactions require activated glycosyl donors in the form of nucleotide sugars to drive processes such as posttranslational modifications and polysaccharide biosynthesis. Most plant cell wall polysaccharides are biosynthesized in the Golgi apparatus from cytosolic-derived nucleotide sugars, which are actively transferred into the Golgi lumen by nucleotide sugar transporters (NSTs ). An exception is UDP-xylose, which is biosynthesized in both the cytosol and the Golgi lumen by a family of UDP-xylose synthases. The NST -based transport of UDP-xylose into the Golgi lumen would appear to be redundant. However, employing a recently developed approach, we identified three UDP-xylose transporters in the Arabidopsis thaliana NST family and designated them UDP-XYLOSE TRANSPORTER1 (UXT1) to UXT3. All three transporters localize to the Golgi apparatus, and UXT1 also localizes to the endoplasmic reticulum. Mutants in UXT1 exhibit ∼30% reduction in xylose in stem cell walls. These findings support the importance of the cytosolic UDP-xylose pool and UDP-xylose transporters in cell wall biosynthesis.